Kinetic Aspects of Ethylene Glycol Degradation Using UV-C Activated Hydrogen Peroxide (H2O2/UV-C) - Timur Fazliev; Mikhail Lyulyukin; Denis Kozlov; Dmitry Selishchev (Molecules)
Ethylene glycol (EG) is a contaminant in the wastewater of airports because it is commonly used in aircraft deicing fluids during the cold season in northern regions. Ethylene glycol by itself has relatively low toxicity to mammals and aquatic organisms, but it can lead to a substantial increase in chemical and biological oxygen demands. The contamination of water with EG facilitates the rapid growth of microbial biofilms, which decreases the concentration of dissolved oxygen in water and negatively affects overall biodiversity. The development of a simple method to decompose EG with high efficiency and low operating costs is important. This study revealed that ethylene glycol can be completely oxidized using UV-C activated hydrogen peroxide (H2O2/UV-C) at a high rate (up to 56 mg L−1 h−1) at an optimum EG:H2O2 molar ratio of 1:10–1:15. Air purging the reaction mixture at 1000 cm3 min−1 increases the EG mineralization rate up to two times because the simultaneous action of UV-activated H2O2 and O2 (H2O2 + O2/UV-C) leads to a synergistic effect, especially at low EG:H2O2 ratios. The kinetics and mechanism of EG degradation are discussed on the basis of the concentration profiles of ethylene glycol and intermediate products.